Peer-Led Team Learning: A Strategy to Enhance Research Productivity and Competence - Cortidor, Amelia L.; Igot, Julius J.; Artiaga, Restilou Q. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Research productivity and competence of teachers play a critical role in promoting evidence-based teaching practices and enhancing the quality of education. Hence, this study aimed to determine the effectiveness of Peer-Led Team Learning (PLTL) in enhancing teachers’ research productivity and competence. A purposive sampling technique was used to select the 110 teacher participants and the pre-experimental research design was utilized. Statistical treatment such as frequencies, percentages, and weighted mean were used to determine research productivity and teachers' competence. Results revealed that more than 98% (108) out of 110 teacher participants had completed their studies, and teachers possess a high level of competence in action research (AR). Competence about context and rationale (60.91%), proposed innovation, intervention, strategy (67.27%), action research questions (56.36%), action research methods (60.00%), results and discussion (54.55%), and work plan (64.55%) are all in a high level of competence. About 44.54% (49) out of 110 teacher participants were in a moderate level of competence, and almost 2% still in a low level of AR competence. The research output is the best indicator and the most concrete manifestation that the teachers are capable and competent in writing and conducting AR. Completed AR output is a positive determinant of the teachers' knowledge and skills in action research. Likewise, PLTL is an effective strategy for enhancing teachers' competence in AR. Recommended that (1) AR competency-enhancement training through Action Research Kumustahan, Assessment, and Technical Assistance (AR-KATA) program be conducted in schools; (2) District-organized and school-based research activities utilizing PLTL strategy be implemented and sustained; and (3) Seminars, training, and development research work-related experience and accomplishments of the teachers be included as one of the criteria in selecting and hiring of teachers.